PENGARUH PENGGUNAAN BAHASA INDONESIA DALAM PENGUNGKAPAN LAPORAN KEUANGAN OLEH NON-AKUNTAN: SEBUAH ANALISIS KUALITATIF BERBASIS LITERATUR - Daffany Viroza; Amelia Kartika; Putri Yasmin; Aril Sharon Saragih; Ayu Nadira Wulandari (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to analyze the impact of using the Indonesian language in financial reporting disclosures, particularly for non-accountants. Using a qualitative literature-based approach, this article identifies how the use of language influences the understanding of financial reports, as well as the challenges faced in simplifying accounting terminology. The literature review results indicate that simplifying language in financial reporting disclosures can improve transparency and comprehension, but there are still difficulties in conveying technical terms accurately without compromising the essence of financial information.This study concludes that the effective use of Indonesian in financial reports can enhance accessibility and trust among non-accountant stakeholders. However, further efforts are needed to simplify technical terms and improve financial literacy to support better financial reporting disclosures.